Photonic‐Plasmonic Coupling Enhanced Fluorescence Enabling Digital‐Resolution Ultrasensitive Protein Detection - Priyash Barya; Yanyu Xiong; Skye Shepherd; Rohit Gupta; Lucas D. Akin; Joseph Tibbs; Hankeun Lee; Srikanth Singamaneni; Brian T. Cunningham (2023)
Assays utilizing fluorophores are common throughout life science research and diagnostics, although detection limits are generally limited by weak emission intensity, thus requiring many labeled target molecules to combine their output to achieve higher signal-to-noise. We describe how the synergistic coupling of plasmonic and photonic modes can significantly boost the emission from fluorophores. By optimally matching the resonant modes of a plasmonic fluor (PF) nanoparticle and a photonic crystal (PC) with the absorption and emission spectrum of the fluorescent dye, a 52-fold improvement in signal intensity is observed, enabling individual PFs to be observed and digitally counted, where one PF tag represents one detected target molecule. The amplification can be attributed to the strong near-field enhancement due to the cavity-induced activation of the PF, PC band structure-mediated improvement in collection efficiency, and increased rate of spontaneous emission. The applicability of the method by dose-response characterization of a sandwich immunoassay for human interleukin-6, a biomarker used to assist diagnosis of cancer, inflammation, sepsis, and autoimmune disease is demonstrated. A limit of detection of 10 fg mL